INTEGRATED ISLAMIC SCHOOLS AS AN ALTERNATIVE TO PRESTIGIOUS SCHOOLS OF CHOICE FOR PARENTS IN BUILDING CHILDREN'S CHARACTER (PIONIR: JURNAL PENDIDIKAN, 2024)
This study aims to explore the role of Integrated Islamic Schools as an alternative to prestigious schools chosen by parents in an effort to build children's character. Integrated Islamic Schools offer a holistic educational approach that integrates Islamic values with the national curriculum, thus providing a balance between knowledge and character building. The main objective of Integrated Islamic Schools is to provide education that not only focuses on academic aspects, but also on the character and moral formation of students. Through a qualitative approach, this study examines parents' views on the effectiveness of Integrated Islamic Schools in educating their children. The results show that parents choose Integrated Islamic Schools because these schools are able to fulfill their expectations of education that not only focuses on academic achievement, but also on the development of children's character. A conducive school environment, the role of competent and dedicated teachers, and diverse extracurricular programs are supporting factors in character building. Integrated Islamic schools are also considered capable of creating an Islamic learning atmosphere and supporting children's moral development. The conclusion of this study is that Integrated Islamic Schools are the right choice for parents who want high-quality education that includes academic and moral aspects, and play an important role in shaping a young generation with noble character and achievements. Keywords: Integrated Islamic School, Education.
Keywords: Integrated Islamic School; Education